Efficacy of a new pathogen‐reduced cryoprecipitate stored 5 days after thawing to correct dilutional coagulopathy in vitro. Issue 5 (4th February 2019) - Cushing, Melissa M.; Asmis, Lars M.; Harris, Rebecca M.; DeSimone, Robert A.; Hill, Shanna; Ivascu, Natalia; Haas, Thorsten
Abstract : BACKGROUND: Fibrinogen supplementation during bleeding restores clot strength and hemostasis. Cryoprecipitate, a concentrated source of fibrinogen, has prolonged preparation time for thawing, a short shelf life resulting in frequent wastage, and infectious disease risk. This in vitro study investigated the efficacy of a new pathogen‐reduced cryoprecipitate thawed and stored at room temperature for 5 days (PR Cryo) to treat dilutional hypofibrinogenemia, compared to immediately thawed standard cryoprecipitate (Cryo) or fibrinogen concentrate (FC). STUDY DESIGN AND METHODS: Ten phlebotomy specimens from healthy volunteers were diluted 1:1 with crystalloid and supplemented with PR Cryo and Cryo (at a dose replicating transfusion of two pooled doses [10 units]) and FC at a dose replicating 50 mg/kg. Changes in clot firmness (thromboelastometry) and in coagulation factor activity were assessed at baseline, after dilution, and after supplementation. RESULTS: Clinical dosing was used, as described above, and consequently the FC dose contained 24% and 36% more fibrinogen versus PR Cryo and Cryo, respectively. At baseline, subjects had a median FIBTEM maximum clot firmness of 13.5 mm, versus 6.5 mm after 50% dilution (p = 0.005). After supplementation with PR Cryo, a median FIBTEM maximum clot firmness of 13 mm was observed versus 9.0 mm for Cryo (p = 0.005) or 16.5 mm for FC (p = 0.005). Median factor XIII was higher after PR Cryo (64.8%) versus Cryo (48.3%) (p = 0.005). Fibrinogen activity was higher after FC (269.0 mg/dL) versus PR Cryo (187.0 mg/dL; p = 0.005) or Cryo (193.5 mg/dL; p = 0.005); the difference between PR Cryo and Cryo supplementation (p = 0.445) was not significant. CONCLUSION: PR Cryo used 5 days after thawing effectively restores clot strength after in vitro dilution.